Pengaruh Literasi Keuangan dan Literasi Digital terhadap Kinerja UMKM Kuliner di Pasar Rebo Jakarta Timur - Eka Lidia Riska; Mardi; Dwi Kismayanti Respati (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to examine the influence of financial literacy and digital literacy on performance through entrepreneurial behavior as a mediating variable among MSME actors in the culinary sector in Pasar Rebo District, East Jakarta. This research is quantitative in nature with a sampling method using the Slovin formula with an error significance level of 5%, so that the results obtained were 348 MSME actors in the culinary sector in Pasar Rebo District, East Jakarta as a sample. Data collection was carried out by distributing questionnaires online to respondents. Data were analyzed using the SmartPLS program version 3.0. The results of this research show that the variables financial literacy and digital literacy have a significant positive effect on performance and through entrepreneurial behavior as a mediating variable for MSME actors in the culinary sector in Pasar Rebo District, East Jakarta. By understanding financial literacy, digital literacy and good and effective entrepreneurial behavior, MSMEs can improve their business capabilities and business performance.